Formulasi Strategi Pengembangan Usaha Susu Sapi Perah - Saeful Yusup, Aep; Purnamawati, Ami; Mulyana, Iwan (Universitas Koperasi Indonesia, 2022)
The KSU Tandangsari Producer Cooperative is a cooperative whose members are dairy milk producers, which produce whole milk. To obtain a number of advantages and take advantage of market opportunities, it is necessary to conduct a comprehensive SWOT analysis with a Business Model Canvas approach. The purpose of this study is to conduct a SWOT analysis to determine both internal and external factors that can affect the dairy cow milk business, find out the position of cooperatives, formulate alternative strategies, set strategic priorities that can be applied and compile the development of a dairy cow milk business model. The method used in this study is a quantitative method with data collection techniques, namely interviews, observations and questionnaires. The results of this study are factors that affect the dairy business, including a high dairy cow population as well as the main force. The main drawback is the limitation of business capital at the breeder level. The main opportunity is a wide market opportunity and the main threat is the high price of additional feed. The position of the dairy cow milk business is in quadrant V which indicates the